ARE THERE 'PRINCIPLES' OF ACCOUNTING? - Lewis, Charles A. (The Accounting Review, 1959)
The accounting profession is expressing much concern over the lay misunderstanding of the meaning and significance of audit reports and especially of the financial statements upon which audit opinions are expressed. Much of the misunderstanding which is causing concern arises from the use by accountants of a technical terminology, the connotations of which are not clear to lay readers of audit reports and financial statements. The evolution of the present short form audit opinion, admirably crystallized by the Committee on Auditing Procedure, has resulted in a statement which is, in most respects, masterful in its specificity in a highly compressed form. The "ultimate source or origin" of many accounting concepts is lost in the mists of antiquity. Variation in accounting methods, produces widely variant results, but still within the scope of "generally accepted accounting principles," even though fully justified by the facts of the cases, has been the source of many structures upon the accounting profession by a number of groups, notably securities analysts, bankers, governmental agencies, labor union research people and businessmen in general.